Optimization of Spot Welding Parameters on Shear Tensile Strength of 0.9 mm SPCC Material using the Taguchi Methods - Samodra, Yudha; Hutama, Adhi Setya; Kurniawan, Perwita; Hayu, Winastwan Sista; Nugroho, Th. Adi (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Resistance spot welding (RSW) is one of the most widely used joining methods for thin metal sheets in the manufacturing industry, particularly for low-carbon steel materials such as SPCC. At PT. XYZ, inconsistencies in weld quality have been observed due to the absence of optimized process parameters. This study aims to analyze the influence of spot welding parameters—welding current, welding time, and holding time—on the shear tensile strength of 0.9 mm SPCC material. The Taguchi method with an L9 orthogonal array experimental design was employed to identify the optimal parameter combination. Shear tensile testing was conducted in accordance with ISO 14273:2016, while data analysis was performed using the Signal-to-Noise (S/N) ratio with the